RichReview++: Deployment of a Collaborative Multi-Modal Annotation System for Instructor Feedback and Peer Discussion - Yoon, D.; Chen, Nicholas; Randles, B.; Cheatle, A.; Jackson, S.; Loeckenhoff, C.; Sellen, Abigail; Guimbretiere, F. (Proceedings of CSCW, 2016)
New multi-modal annotation tools hold the promise of bringing the benefits of face-to-face contact to remote, asynchronous interactions. One such system, RichReview++, incorporates new techniques to improve access to the embedded multimedia commentary and allows users to annotate with new modalities, like deictic gestures. We conducted a series of field deployments of RichReview++ to characterize how these features benefit students using them for activities in the university classroom. Our first deployment investigated the use of multi-modal annotations as a way for instructors to provide feedback on student term papers. Our second deployment used annotations to support peer discussion about assigned readings in a graduate-level course. We found that presenting voice comments as interactive waveforms seems to facilitate students’ consumption of the instructor’s voice comments. We also found that gestural annotations clarify voice and give annotators a quick and lightweight way to alter the scope of their voice comments. Based on these results, we suggest ways to best leverage multi-modal annotation tools in education environments.